Planificación Participativa para la reducción del riesgo de desastres: rutas de aprendizaje para reducir la brecha entre estado y territorio - Recharte, Jorge; Rondán Ramírez, Vidal (Pontificia Universidad Católica del Perú, 2024)
This case study discusses a problem identified in the global literature: the difficulty of national states in translating their policy instruments for disaster risk reduction and climate change adaptation into effective actions at the local territorial level. We review two perspectives on the territory and modes of intervention: (i) those of government agencies within the Huascarán Biosphere Reserve in Áncash and (ii) those deployed by local organizations in the context of a disaster risk reduction project. The case study presents evidence on the potential of participatory approaches to generate information that can help identify strategies that align adaptation and risk reduction actions to local well-being objectives and productive systems. It is concluded that there is a need to develop collaborative learning spaces between state agencies and communities to improve the effectiveness of policy instruments for disaster risk reduction.

El estudio de caso discute un problema identificado en la literatura global: la dificultad de los Estados nacionales de traducir instrumentos de política para la reducción del riesgo de desastres y adaptación al cambio climático en acciones efectivas al nivel del territorio local. Revisamos dos ópticas del territorio y modos de intervención: (i) las de las agencias de gobierno en el ámbito de la Reserva de Biosfera Huascarán en Áncash (ii) y las que despliegan organizaciones locales en el contexto de un proyecto de gestión de riesgo de desastres. El estudio de caso presenta evidencia sobre el potencial de enfoques participativos para generar información que permita identificar estrategias que articulen acciones de adaptación y reducción del riesgo a los objetivos de bienestar y los sistemas productivos locales. Se concluye que existe la necesidad de desarrollar espacios de aprendizaje colaborativo entre agencias del Estado y comunidades para mejorar la efectividad de instrumentos de política para la reducción del riesgo de desastres.
Participatory planning for disaster risk reduction: learning pathways to bridge the gap between state and territory
Keywords: Socio-ecosystems; Transformative change; Resilience; Public action; Conservation; ECO-DRR; Mountain; Andes; Ancash; Peru; Socioecosistemas; Cambio transformativo; Resiliencia; Acción pública; Conservación; ECO-RRD; Montaña; Andes; Áncash; Perú; https://purl.org/pe-repo/ocde/ford#2.07.01